Solar power for energy sustainability and environmental friendliness of Curtin University Sarawak. Issue 1 (March 2016) - Palanichamy, C; Goh, Alvin
Abstract: The demand on electrical energy is rapidly increasing. Everything around us requires electrical energy either during its production or usage stage. Sustainability has become the main concern nowadays as the availability of fossil fuels is limited. As renewable energy is the path-way to energy sustainability and environmental friendly environment, this paper proposes a solar power system for Curtin University Sarawak to reduce its electricity consumption and greenhouse gas emissions. The proposed 208 kW solar system saves an energy consumption of more than 380, 000 kWh per year, and a CO2 offset by 285 Tons per year